Study of glycemic status and lipid profile in type 2 diabetic patients attending the Community Based Medical College Hospital - Rahman, Md Muzibar; Hassan, Zahid; Sen, Bina; Shahidullah, ASM; Paul, Arup Ratan; Saha, Kamana Rani (Community Based Medical Journal, 2014)
A cross sectional study of 129 type 2 diabetic patients attending out patient department of Community Based Medical College Hospital was done with an aim to evaluate their metabolic control. Of the total cases, 88 (68.2%) were male and 41 (31.8%) were female. Blood glucose and lipid levels were measured by following the standard laboratory methods. The study subjects had relatively poor glycemic control. Fasting serum glucose was 7.45±2.71 (mmol/l, mean±SD); Male-7.04±2.36 and Female 8.33±3.20, p=ns'. Mean (±SD) of total cholesterol and triglyceride of the female subjects were significantly higher compared to the male counterpart (p=0.01 for both). About 71% and 78.0% female subjects had triglyceride and HDLc abnormality compared to 63.3% and 61.4% respectively in their male counterpart. Fasting glucose level showed significant positive correlation with triglyceride among total and male study subjects (p=0.003 for both). In case of total cholesterol significant positive association was among total and female subjects (p=0.005 and 0.007 respectively). The data concluded that (i) relatively large number of diabetic patients were having dyslipidemia of either component or in combination; and (ii) attention needs to be paid to address this issue of dyslipidemia and to avoid or at least delay the coronary artery and atherosclerotic complications of these subjects. CBMJ 2014 January: Vol. 03 No. 01 P: 20-24